2011
DOI: 10.1155/2011/467083
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Shape Changes of TiO2Nanocrystals Synthesized by Microemulsion-Solvothermal Method

Abstract: Titanium dioxide (TiO2) nanocrystals of different shape were successfully synthesized in a new microemulsion system through a solvothermal process. The TiO2nanocrystals were prepared from the reaction of tetrabutyl titanate (TBT),H2O, and oleic acid (OA), which were used as solvent and surfactant at 300∘Cand 240∘Cin a stainless steel autoclave. The sphere, polygon, and rhombus-shaped nanocrystals have been prepared at 300∘Cand the dot- and- rod shaped nanocrystals have been synthesized at 240∘C. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…00-001-0562, these TiO 2 NPs have a tetragonal anatase phase. [24][25][26] Using Scherer's approach, 27,28 the TiO 2 NPs crystallite size (L) can be computed from:…”
Section: Xrd and Tem Analysismentioning
confidence: 99%
“…00-001-0562, these TiO 2 NPs have a tetragonal anatase phase. [24][25][26] Using Scherer's approach, 27,28 the TiO 2 NPs crystallite size (L) can be computed from:…”
Section: Xrd and Tem Analysismentioning
confidence: 99%
“…5). [49], sono-chemical synthesis [50], reverse micro-emulsion [51], pyrolysis-assisted melting of salts [52], hydrothermal synthesis [53][54][55] of titanium dioxide-based rod-shaped nanostructures. The advantage of this method is that nanotubes or nanowires can be obtained in relatively large quantities.…”
Section: Methods Of Synthesizing Na 2 Ti 3 O 7 and Obtaining Nanotubementioning
confidence: 99%
“…In such a mechanism, the crystal surface energy played an important role for the shape of the nanocrystals. Due to the high surface energy of {001} face, the spherical nanocrystal generated at the initial reaction stage grow along the (001) direction [25].…”
Section: Characterization Of the Samplesmentioning
confidence: 99%
“…However, a careful high magnification TEM analysis of the nanorods demonstrated that, along with preferential growth, another rod mechanism formation could exist: oriented attachment mechanism (inset of Figure 3a). The oriented attachment mechanism has been reported for a variety of metal oxide systems and, in particular, for the crystalline anatase TiO 2 nanorods, by the reaction [12] between TiCl 4 and benzyl alcohol at 80°C and by the reaction [25] of tetrabutyl titanate (TBT), H 2 O and oleic acid at 240°C. It is said that the oriented attachment between spherical nanocrystals reduces the surface energy and can usually be observed in (001) direction because of its high surface energy [12].…”
Section: Characterization Of the Samplesmentioning
confidence: 99%